Experiences of mistreatment among medical students in a University in South West Nigeria (2012)
Objective: This study was conducted to assess the experiences of mistreatment and harassment among final-year clinical students in a Nigerian medical school. Materials and Methods: A self-administered questionnaire was used to obtain information on the various forms of mistreatment experienced by 269 students in the 2007 and 2008 graduating classes of a medical school in Nigeria. Results: Almost all the respondents (98.5%) had experienced one or more forms of mistreatment during their training. The commonest forms experienced by the students were being shouted at (92.6%), public humiliation or belittlement (87.4%), negative or disparaging remarks about their academic performance (71.4%), being assigned tasks as punishment (67.7%), and someone else taking credit for work done by the student (49.4%). Religious or age discrimination was reported by 34.2%, sexual harassment and other forms of gender-based mistreatment by 33.8%, and threats of harm by 26.4%. These incidents were mainly perpetrated by physicians and occurred mostly during surgical rotations. The effects included strained relationships with the perpetrators, reduced self-confidence and depression. Conclusion: Most medical students experienced verbal forms of mistreatment and abuse during their training. Appropriate strategies for the prevention and reduction of medical student mistreatment should be developed.